تأثير التدريب بالأثقال التخصصي في تنمية القدرة العضلية على فعالية الأداء المهاري لمرحلة الرمي (الإلقاء) لدى ناشئي رياضة الجيدو - بن برنو, عثمان; إدريس خوجة , محمد رضا; حجار , خرفان محمد (Journal of Sport Science Technology and Physical Activities, 2025)
The research aims to the following: - Knowledge of the effectiveness of the proposed weights training program in the development of power (the ability of muscle) in judo wrestlers. - Knowledge of the effectiveness of the proposed weights training program to increase the effectiveness of the performance skills of judo wrestlers The researchers used the experimental method on a sample of wrestlers, judo has been selected sample way intentional of teams judo State Mostaganem, which numbered 20 famous males of the same weight (less than 66 kg), and years of training (more than 3 years of training) and the degree of the belt (blue, brown)and have never weights training. The sample was divided into two groups, one experimental and included (10 Gladiators) and another officer included (10 Gladiators). It also adopted the researchers on a variety of means to collect information related to the study Kalmkablat personal and test and measurement program was developed training weights proposed in the development of power and increase the effectiveness of performance skills on the experimental group The control sample was applied training program traditional., And the training program for the sample pilot 3 training units per week, the program has been divided into three sessions of the medium (monthly), a period of incorporation, and the period of preparation, and the pre-competition period. Researchers relied on a set of statistical means the following: (validity and reliability coefficient using Bryson equation "t" (for legalization of tests), the arithmetic average, standard deviation, the Test "T" (in the study of semantics). The researchers concluded the following: Shown by the results of statistical tests the ability of muscle and skill on the existence of statistically significant differences in the results of the tests for the experimental group., Which demonstrated the effectiveness of the proposed weights training program, both in the development of power and increase the effectiveness of performance skills